Research on Solution of Mobile Application Always Keeping Online Without Heartbeat - Yao He; Rong Zhang (Dianxin kexue)
Abastract:Along with the mobile application of the increasingly rich, especially widely used as WeChat, QQ and Weibo, the wireless network air interface signaling resource consumption issues highlighted, while the terminal energy consumption. Based on the analysis of the same industry solution, a new no heartbeat solution which can still maintain a mobile application always online was proposed, the wireless command consumption problem was solved.